Introducing Mulato Hybrid Grass as an Alternative High-Quality Forage Source for Ruminants in the Bakti Mekar Jaya Forest Farmer Group, Bojongsoang District, Bandung Regency - Wulansari, Asri; Mayasari, Novi; Firmansyah, Indra; Ismiraj, Muhammad Rifqi (Unpad Press, 2025)
Breeding, feeding and management are important components of the success of a livestock business. Feeding, especially in providing feed with good quantity, quality and continuity, is one of the biggest inputs and challenges in livestock business. Until now, providing feed, especially forage, is still a big challenge in ruminant livestock farming. Mulato grass is a potential alternative forage source because it has good quality, is drought resistant, has high biomass, and is popular with livestock. This community activity (PKM) aims to announce hybrid mulato grass to breeders as a potential forage alternative for ruminants. The object or target in this community service activity is the Bakti Mekar Jaya Forest Farmers Group. The counseling method was used in this activity. The stages of implementing activities consisted of the preparation stage, assessment stage (pre-test), counseling stage and evaluation stage (post test). The results achieved in this extension activity provide benefits for livestock, including: (1) obtaining alternative sources of forage for the livestock being kept; (2) minimizing the risk of a shortage of forage during the dry season; (3) gain knowledge about cultivating hybrid mulato grass. The continued phase of this PPM activity involves observing the development of Mulato hybrid grass to serve as a supplementary feed source.